Urinary Neopterin and Microalbuminuria in Patients Treated by Low-density Lipoprotein Apheresis - Cermanová Melanie (Pteridines, 2005)
Low-density lipoprotein (LDL)-apheresis is a method of extracorporeal elimination of LDL-cholesterol in patients with severe primary lipoprotein disorders. LDL-cholesterol activates macrophages, which play an important role in atheromatous plaque formation. In the present study, we have investigated urinary neopterin, a specific marker of macrophage activation and microalbuminuria, an indicator of generalized vascular dysfunction, after a single LDL-apheresis procedure in 10 patients with severe primary lipoprotein disorder. The urinary neopterin/creatinine ratio was increased in patients compared to controls. No significant changes of the neopterin/creatinine and albumin/creatinine ratios were observed after LDL-apheresis, except a significant (p < 0.006) decrease of urinary neopterin/creatinine ratio in the evening after the apheresis. This decrease showed significant negative correlation with the pre-apheretic levels of atherogenic cholesterol fractions (p < 0.05) and with cholesterol decrease during the apheresis (p < 0.05). Urinary albumin/creatinine ratio correlated positively with total and LDL-cholesterol levels before the apheresis and with the evening urinary neopterin/creatinine ratio after the apheresis, but did not correlate with glycemia and triacylglycerides. Elevated urinary neopterin in the patients with severe primary lipoprotein disorders reflects the presence of atherosclerosis. A single LDL-apheresis procedure did not significantly affect microalbuminuria. The decrease of urinary neopterin in the evening after the apheresis corresponds with the diurnal rhythm of neopterin excretion and was less pronounced in patients with more severe hypercholesterolemia. The correlations between microalbuminuria, neopterin and pre-apheretic cholesterol concentrations indicate a possible connection between microvascular dysfunction, macrophage activity and severity of hyperlipidemia, but these results should be interpreted with caution because of small number of subjects evaluated.